PEREMPUAN DALAM KAMPANYE ANTIKORUPSI - Fitri Yuliantri Permana (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2017)
Komisi Pemberantasan Korupsi (KPK) drafted a social movement Saya Perempuan ANtikorupsi (SPAK) by involving the strategic role of women as campaign communicators. This research will discuss how anti-corruption campaign process through SPAK Movement on Dharma Wanita Persatuan Kementerian Agama Indonesia (DWP Kemenag). The research was conducted with case study methodology during the April 2016-April 2017 campaign period in the central ministry’s DWP and regional offices. Based on the results of the research, some characteristics of the SPAK movement in DWP Kemenag are the women’s campaign style which emphasizes the role of women as the moral guardians of husbands and families, the presence of key organizational advisors as the main supporters of the campaign, and massive campaign spread resulting from existing organizational structures up to the root level grass. The results of this study are expected to be a model picture of anti-corruption campaigns conducted in the bureaucratic environment through the strategic role of women.